TRANSLATION TECHNIQUES AND QUALITY VALUES OF ACCURACY, ACCEPTABILITY AND READABILITY IN THE “KITAB SYARAH USFURIAH” - Tatik Irawati; Aang Fatihul Islam (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Some of the errors in translating kitab are improper matching in the target language (TL), adding words or phrases beyond the source text, shifts in word level, omission of equivalent words and phrases, and errors identifying words in the source language (SL). The purpose of this study is to explain the translation process by analyzing the translation techniques that often appear in the Kitab Syarah Usfuriah and assessing the quality of the translation results on accuracy, acceptability and readability. This study uses a qualitative method. The subject of this research is the translation of Kitab Syarah Usfuriah by choosing two hadiths, namely the fourth hadith about the virtue of seeking knowledge and the forty hadith about people of the end of time. The translation technique used in this study is adaptation is used to replace the existing cultural elements in the source language (SL) into cultural elements similar to the target language (TL). Borrowing translation technique take a word or expression straight from another language. Established equivalent by translating the source language expressions into expressions that are commonly used in the target language (TL), and the terms of those expressions can include phrases, clauses, and idiomatic expressions. Literal translation by translating the source language (SL) text as it is without paying attention to context. Particularization which uses more concrete terms and special. The quality of the translation results each scored 3 on accuracy, acceptability and readability.